Thirty years of economic policy : inspiration for debate - Wyplosz, Charles (Oxford University Press, 2015)
A volume to mark the 30th anniversary of the journal Economic Policy. It brings together key articles that still matter today, and provides academics with important research markers. It also acts as a student reader that demonstrates how the field of economics progresses by responding to challenges of the time.